Identifying anxiety and sleep problems, associated factors and sex differences in endurance and ultra-endurance runners - Scheer, Volker; Valero, David; Valero, Encarna; Weiss, Katja; Rosemann, Thomas; Knechtle, Beat (Frontiers in Psychology, 2025)
BackgroundAnxiety and sleep problems may negatively impact health and athletic performance.MethodsWe conducted a cross-sectional survey study in endurance (≥21.1–42.2 km) and ultra-endurance runners (≥42.2 km), screening for anxiety and sleep problems, assessing potential associated factors and sex differences. Statistical methods included descriptive statistics, testing of group differences with the Kruskal-Wallis H-test, and Dunn’s post-hoc tests, allowing for Bonferroni correction for multiple comparisons, predictive techniques, and regression analysis.ResultsA total of 601 runners participated (female n = 222; male n = 379; mean age 42.8 ± 10.1 years). Overall, 13.5% screened positive for anxiety (female 16.2% compared to men 11.9%; n.s.) and 28.8% for sleep problems (female 32.9% compared to men 26.4%; n.s.). Anxiety and sleep problems were observed significantly more often in half marathon runners (25.2%; (p < 0.001) and 38.3%, (p = 0.02), respectively) compared to marathon (9.8 and 28.4%) and ultramarathon distance runners (11.1 and 28.2%). No statistical differences were found between sexes and performance levels (elite versus non-elite). Associated factors for anxiety included sleep problems (p < 0.001), younger age (<29 years; p < 0.001), years practicing the sport (>10 years; p = 0.006), and distance category (p = 0.03). Associated factors for sleep problems included anxiety (p < 0.001), competition frequency (>4 per year; p = 0.006), and injury-related absences (p = 0.001).ConclusionMental health issues, such as anxiety and sleep problems are common in endurance and ultra-endurance runners and positive screening for anxiety co-existed and was associated with positive screening for sleep problems. This study demonstrates that identifying and screening for anxiety and sleep problems is important, as well as the need for creating awareness, education, preventative strategies, and support services.